Management Accounting Systems and Credit Risk Management Policies and Practices towards Organizational Performance in Palestinian Commercial Banks - Thabet, Ahmed; Alaeddin, Omar (International Journal of Engineering and Technology, 2018)
The aim of this paper is to report the results of a study on the linkages between credit risk management (CRM) policies and practices and management accounting system (MAS) toward organizational performance through testing the match and joint effects of MAS and CRM on organizational performance. The research method involved two data collection methods. Firstly, this study implemented an empirical investigation for the relationship between credit risk management policies and profitability of commercial banks in Palestine over the period of 7 years (2008-2014), eleven commercial banks were selected. The financial theory was employed to create the research model; Return on Asset (ROA) and Return on Equity (ROE) are defined as proxies of profitability while capital adequacy (EQTA), credit monitoring (LLPI), income diversification (NIDR) and operational performance efficiency (DTL) are defined as proxies of credit risk management.Â Panel model analysis was used to estimate the determination of the profit function. Secondly, administering a questionnaire to 11 commercial banks listed on the Palestinian Monetary Authority website and the respondents were those in the risk management department on banks such as chief executive officers (CEOs), chief risk officers (CROs), chief financial controllers, general managers, risk managers, and bank employees at departments related to risk management in Palestinian commercial banks. Based on the IFACâ€™s (1998) framework and the Bank of International Settlement report (2013), results revealed that the credit risk management does have significant effect on the both ROA and ROE, While EQTA has a negative insignificant effect on ROA. However, the relationships between all the proxies are fluctuated. In light of the relationship between CRM practices and MAS toward organizational performance, Integration between costing system, Budgeting and information for decision making MAS Ã— CRM Policies is positively associated with organizational performance. Likewise, some management accounting practices works to assist in managing credit risks in two main dimensions costing system and budgeting. The finding also confirms the important role of interaction between CRM, MAS and organizational performance.Â Â